Inhibitory Effects of Macrotetrolides from Streptomyces spp. On Zoosporogenesis and Motility of Peronosporomycete Zoospores Are Likely Linked with Enhanced ATPase Activity in Mitochondria - Islam, Md. Tofazzal; Laatsch, Hartmut; von Tiedemann, Andreas (Frontiers in Microbiology, 2016)
The release of zoospores from sporangia and motility of the released zoospores are critical in the disease cycle of the Peronosporomycetes that cause devastating diseases in plants, fishes, animals and humans. Disruption of any of these asexual life stages eliminates the possibility of pathogenesis. In the course of screening novel bioactive secondary metabolites, we found that extracts of some strains of marine Streptomyces spp. rapidly impaired motility and caused subsequent lysis of zoospores of the grapevine downy mildew pathogen Plasmopara viticola at 10 g/ml. We tested a number of secondary metabolites previously isolated from these strains and found that macrotetrolide antibiotics such as nonactin, monactin, dinactin and trinactin, and nactic acids such as (+)-nonactic acid, (+)-homonactic acid, nonactic acid methyl ester, homonactic acid methyl ester, bonactin and feigrisolide C impaired motility and caused subsequent lysis of P. viticola zoospores in a dose- and time-dependent manners with dinactin being the most active compound (MIC 0.3 g/ml). A cation channel-forming compound, gramicidin, and a carrier of monovalent cations, nigericin also showed similar biological activities. Among all 12 compounds tested, gramicidin most potently arrested the motility of zoospores at concentrations starting from 0.1 g/ml. All macrotetrolide antibiotics also displayed similar motility impairing activities against P. viticola, Phytophthora capsici and Aphanomyces cochlioides zoospores indicating non-specific biological effects of these compounds towards peronosporomyctes. Furthermore, macrotetrolide antibiotics and gramicidin also markedly suppressed the release of zoospores from sporangia of P. viticola in a dose-dependent manner. As macrotetrolide antibiotics and gramicidin are known as enhancers of mitochondrial ATPase activity, inhibition of zoosporogenesis and motility of zoospores by these compounds are likely linked with hydrolysis of ATP through enhanced ATPase activity in mitochondria. This is the first report on motility inhibitory and lytic activities of macrotetrolide antibiotics and nactic acids against the zoospores of peronosporomycete phytopathogens.